2019
DOI: 10.1111/saje.12240
|View full text |Cite
|
Sign up to set email alerts
|

National and Regional Impacts of an Increase in Value‐Added Tax: A CGE Analysis for South Africa

Abstract: The South African National Treasury expected a revenue shortfall of R48.2 billion in 2017/18 and proposed tax policy measures to raise an additional R36 billion in 2018/19. A key component to raise the additional revenue was a 1% point increase in the VAT rate to 15% effective from 1 April 2018. The increase in the VAT rate was not welcomed as it would increase the cost of living, especially for the poor. We investigate the potential economy‐wide and regional impacts of raising VAT and increasing public spendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…However, the high prevalence and pattern of overweight and obesity among WCBA reported in this paper means the government needs to complement the sugar-sweetened beverage tax with other policies to address overweight and obesity. Although many essential food items, including "healthy" food items, are exempted from valueadded tax in South Africa [82], they could be further subsidised to increase accessibility and availability [2]. There is also a need for awareness-raising campaigns promoting healthy eating and lifestyles among WCBA [21], bearing in mind that the risk of obesity increases with age.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…However, the high prevalence and pattern of overweight and obesity among WCBA reported in this paper means the government needs to complement the sugar-sweetened beverage tax with other policies to address overweight and obesity. Although many essential food items, including "healthy" food items, are exempted from valueadded tax in South Africa [82], they could be further subsidised to increase accessibility and availability [2]. There is also a need for awareness-raising campaigns promoting healthy eating and lifestyles among WCBA [21], bearing in mind that the risk of obesity increases with age.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Ref. [36], used a CGE model to study the increase by 1 percent of the VAT in South Africa, and found that it affected not only the cost of living (i.e., consumers) but also the short-run cost to the employer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An average value over all industries for the sensitivity of capital growth to variations in expected rates of return is used as a proxy, denoted by the term S_KGR_ERoRt in (EQ27). We base our estimates for these parameters on those used in Roos et al (2020). Source: authors' elaboration based on Dixon and Rimmer (2002: 191).…”
Section: Rate Of Inflation In Year Tmentioning
confidence: 99%